The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1603/ec10022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Resistance in Seeds of Different Soybean Cultivars to <I>Helicoverpa armigera</I> (Lepidoptera: Noctuidae) Using Demographic Parameters and Nutritional Indices

Abstract: The use of resistant cultivars is a key component of any integrated pest management (IPM) program. Here, we assess the resistance status of 10 different soybean cultivar seeds according to their effects on demographic and nutritional indices of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) when incorporated into artificial diets. All experiments were conducted at 25 +/- 1 degrees C, 60 +/- 5% RH, and a photoperiod of 16:8 (L:D) h. Life table, reproduction, development, adult longevity, and nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…According to the results (Soleimannejad et al, 2010), there was strong effect of the seeds of different soybean cultivars on development time of H. armigera when incorporated into artificial diet (Table 8). The larvae reared on Clark and Sari had comparatively shorter development time of immature stages which was more than the value (29.7 days on cotton) previously reported on different hosts by Liu et al (2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results (Soleimannejad et al, 2010), there was strong effect of the seeds of different soybean cultivars on development time of H. armigera when incorporated into artificial diet (Table 8). The larvae reared on Clark and Sari had comparatively shorter development time of immature stages which was more than the value (29.7 days on cotton) previously reported on different hosts by Liu et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…The artificial diet contained: soybean seed powder (250 g), wheat germ (30 g), yeast (35 g), sorbic acid (1.1 g), ascorbic acid (3.5 g), sunflower oil (5 ml), agar (14 g), methyl-p-hydroxy benzoate (2.2 g), formaldehyde 37% (2.5 ml) and distilled water (650 ml) (Teakle, 1991). The prepared artificial diets were kept refrigerated for no longer than two weeks before use (Soleimannejad et al, 2010). The experimental conditions to determine the life table parameters of H. armigera were the same as the previously described conditions on the pods of soybean cultivars (see the section 2.2).…”
Section: Case Study 411 Experimental Conditionsmentioning
confidence: 99%
“…Different effects by a variety of host plants have been reported for several other pest insects, including Helicoverpa armigera (Soleimannejad et al. ; Soufbaf et al. ) and Spodoptera litura (Bae and Park ).…”
Section: Discussionmentioning
confidence: 98%
“…The host plant availability and quality affect both larval and adult development either positively or negatively. Different effects by a variety of host plants have been reported for several other pest insects, including Helicoverpa armigera (Soleimannejad et al 2010;Soufbaf et al 2010) and Spodoptera litura (Bae and Park 1999). The development and survival rates of Plutella xylostella and Pieris brassicae vary on different host plants, which correspond with plant suitability for these herbivores Ansari 2010a,b,c, 2011;Saeed et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the fertility life table, for the net reproduction rate (R 0 ), Truzi et al [24] found a higher value for the artificial diet, with 255 females per female in each generation. For soybean cultivars, the rate ranged from 16.0 to 270.0 females per female [29], while for tomato cultivars, it was between 7.8 and 186.9 females per females [30]. The average generation time (T) was influenced by the protein content, and at lower protein levels, the insects took longer to complete the cycle.…”
Section: Discussionmentioning
confidence: 99%